Non-Conviction Based Asset Forfeiture sebagai Solusi Kredit Bermasalah Akibat Tindak Pidana Perbankan: Studi Perbandingan Indonesia, Amerika Serikat, dan Thailand - Nurhalimah, Siti (LPPAIK Universitas Muhammadiyah Bandung, 2025)
Non-performing loans (NPLs) resulting from banking crimes pose a significant threat to financial system stability. In many cases, conventional recovery mechanisms such as collateral execution or criminal proceedings fail to effectively return misappropriated assets. This article explores the concept of Non-Conviction Based Asset Forfeiture (NCBAF) as an alternative legal instrument for asset recovery without the necessity of a criminal conviction, particularly in the banking sector. Utilizing a comparative legal approach between Indonesia, the United States, and Thailand, along with the theoretical framework of Economic Analysis of Law and responsive law theory, this study evaluates the urgency of asset recovery reform in Indonesia. The findings indicate that NCBAF can accelerate asset recovery from banking-related crimes while enhancing legal efficiency and reducing state burdens. The article recommends adapting the NCBAF framework in the Draft Law on Asset Forfeiture and establishing an independent asset management institution.